Recent Global Research and Education: Technological Challenges Proceedings of the 15th International Conference on Global Research and Education Inter-Academia 2016 - Jabłoński, Ryszard; Szewczyk, Roman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Developments in the connected fields of solid state physics, bioengineering, mechatronics and nanometrology have had a profound effect on the emergence of modern technologies and their influence on our lives. In all of these fields, understanding and improving the basic underlying materials is of crucial importance for the development of systems and applications. The International Conference  Inter-Academia 2016 has successfully married these fields and become a regular feature in the conference calendar. It consisted of seven thematic areas in the field of material science, nanotechnology, biotechnology, plasma physics, metrology, robotics, sensors and devices. The book Recent Global Research and Education: Technological Challenges  is intended for use in  academic, government and industry R&D departments, as an indispensable reference tool for the years to come. Also, we hope that the volume can serve the world community as the definitive reference sourcein Advances in Intelligent Systems and Computing. This book comprises carefully selected 68 contributions presented at the 15th International Conference on Global Research and Education INTER-ACADEMIA 2016, organized by Faculty of Mechatronics, Warsaw University of Technology, on September 26-28, in Warsaw, Poland. It is the second volume in series, following the edition in 2015. It brings together the knowledge and experience of 150 leading researchers representing 13 countries. We would like to thank all contributors and reviewers for helping us to put-together this book.
Keywords: Computational intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Applied Dynamical Systems